2018
DOI: 10.1111/cts.12570
|View full text |Cite
|
Sign up to set email alerts
|

Assay Guidance Manual: Quantitative Biology and Pharmacology in Preclinical Drug Discovery

Abstract: The Assay Guidance Manual (AGM) is an eBook of best practices for the design, development, and implementation of robust assays for early drug discovery. Initiated by pharmaceutical company scientists, the manual provides guidance for designing a “testing funnel” of assays to identify genuine hits using high‐throughput screening (HTS) and advancing them through preclinical development. Combined with a workshop/tutorial component, the overall goal of the AGM is to provide a valuable resource for training transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…3C ) showed that EC 50 values averaged 290 nM and 65% of values varied by no more than threefold from the mean (a range considered acceptable for most cell-based assays). 34,35 This performance was considered modest but acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…3C ) showed that EC 50 values averaged 290 nM and 65% of values varied by no more than threefold from the mean (a range considered acceptable for most cell-based assays). 34,35 This performance was considered modest but acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…It is not subject to copyright under 17 USC 2). Three critical assay design parameters, based on the NCATS Assay Guidance Manual, were selected for optimization: reaction time, substrate concentration, and enzyme concentration [15,16].…”
Section: Papain Cell-free Enzymatic Assaymentioning
confidence: 99%
“…NCATS arms researchers with translational science information by making new methods, data, and information publicly available. For instance, the Assay Guidance Manual (AGM), as a procedure for data transparency and release in NCATS, resulted in the successful development of robust, early-stage drug discovery assays [ 62 ]. In addition, in the case of the availability of data, NCATS serves the pharmacological industry through PubChem [ 63 ] (small organic molecules and their activities against biological assays), the NCATS pharmaceutical collection [ 64 ] of active pharmaceutical ingredients and small molecules, and small molecule probes [ 65 ].…”
Section: Computational- and Wet Lab-based Assay Dbsmentioning
confidence: 99%